2014
DOI: 10.1063/1.4869668
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative link between work of adhesion and thermal conductance of metal/diamond interfaces

Abstract: We report Time-Domain ThermoReflectance experiments measuring the Thermal Boundary Conductance (TBC) of interfaces between diamond and metal surfaces, based on samples consisting of [111] diamond substrates with hydrogen or with sp 2 carbon surface terminations created using plasma treatments. In a concurrent theoretical study, we calculate the work of adhesion between Ni, Cu and diamond interfaces with [111] surface orientation, with or without hydrogen termination of the diamond surface, using first-principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 76 publications
2
31
0
Order By: Relevance
“…Using this technique on metal/diamond systems, the diamond surface chemistry was shown to have a strong impact on the TBC between diamond and metals [23][24][25]. Hydrogen-terminated diamond surfaces were found to always be detrimental to obtaining high TBC [18,24]. This was rationalized by the fact that hydrogen termination also lowers the metal/diamond work of adhesion, thereby weakening the bonds between metal and diamond [18].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Using this technique on metal/diamond systems, the diamond surface chemistry was shown to have a strong impact on the TBC between diamond and metals [23][24][25]. Hydrogen-terminated diamond surfaces were found to always be detrimental to obtaining high TBC [18,24]. This was rationalized by the fact that hydrogen termination also lowers the metal/diamond work of adhesion, thereby weakening the bonds between metal and diamond [18].…”
Section: Introductionmentioning
confidence: 80%
“…Hydrogen-terminated diamond surfaces were found to always be detrimental to obtaining high TBC [18,24]. This was rationalized by the fact that hydrogen termination also lowers the metal/diamond work of adhesion, thereby weakening the bonds between metal and diamond [18]. By using an oxygen plasma treatment of the diamond surface, it was shown that both a good adhesion and a high TBC can be obtained between a metal and diamond [24,25].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has recently been shown that the nature and the strength of the chemical bond have a direct influence on the heat transfer coefficient [1,2]. Hence, improving the bonding between matrix and inclusion phases and therefore heat transfer across the interface may give access to an overall improved thermal conductivity of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…welldefined plain and large synthetic diamond monocrystal surfaces with sputtered layers of Al and other metals creating a carbide-forming interlayer. The ITC is then calculated by means of TDTR time-domain thermoreflectance experimental setup [10,11,15]. In [14] the positive influence of oxygenation on ITC was for the first time shown to be true in the low (4 K) to ambient temperature range for a Ag3Si/diamond system, fabricated under typical ''messier'' lab-scale conditions of gas pressure infiltration using synthetic diamond particles.…”
Section: Introductionmentioning
confidence: 99%